Needs Analysis for a Deep Learning-Based Problem-Based Learning (PBL) Model in Primary School IPAS Subjects - Berty Yustiani; Umi Chotimah; Makmum Raharjo (Postgraduate, University of Mataram, 2026)
The modern curriculum necessitates a fundamental shift in IPAS instruction from rote memorization to deep learning of concepts; however, field implementation often remains superficial. Furthermore, while the Problem-Based Learning (PBL) model is effective, teachers frequently encounter constraints in designing contextual scenarios that ensure that deep learning occurs. Consequently, this research aims to analyze the specific necessities for developing a PBL model based on deep learning for primary school IPAS subjects. This qualitative descriptive study involved 32 teachers and 171 Grade 4 students at primary schools, utilizing comprehensive questionnaires to assess needs across cognitive, pedagogical, technical, socio-cultural, and evaluative dimensions. The analysis reveals that all surveyed aspects fall into the “High Need” category. Specifically, teachers prioritized evaluation (97.75%) and pedagogical (93.35%) aspects, highlighting a critical demand for increased competence in authentic assessment and innovative strategies. Similarly, students indicated urgent needs in evaluative (97.07%) and technical (94.38%) domains. These findings confirm a significant gap in current instructional practices. It is concluded that developing a PBL–Deep Learning model that integrates local socio-cultural contexts with authentic, supportive evaluation instruments is essential to enhance students' conceptual mastery and facilitate effective teaching.